Development Of Ultra Convolution Neural Network For Early Alzheimer’s Disease Detection For Brain Tumor Patients Using Mr Image Analysis (Journal of Pharmaceutical Negative Results, 2023)
Alzheimer’s disease (AD) is slowly growing intense effect disease and causes brain shrinkage and various neurological disorders. The core cause is the buildup of tau and amyloid protein around the brain cells. As detection of AD is a crucial task as AD takes years to get detected. If untreated and/or not diagnosed early, a person can enter into a mild stage with slight forgetfulness. At this stage, it is clinically considered that the AD initiated 10 years ago. Hence, this paper presents the newly developed algorithm ultraCNN for early detection of AD for patients with a brain tumor using brain MR image dataset BRATS. Neural networks are a powerful means for fast detection of brain anatomical changes in brain dimensions. In the case of radiological image interpretation, there can be a human error. The proposed algorithm gives exact results by de-blurring of MR images. So, the proposed algorithm can be helpful for medical experts to predict and diagnose AD very fast.